2017
DOI: 10.1111/pai.12836
|View full text |Cite
|
Sign up to set email alerts
|

Trajectory of spirometric and exhaled nitric oxide measurements in Chinese schoolchildren with asthma

Abstract: Asthmatic children have annual decline in FVC and increase in FEV /FVC and FEF . Their lung function trajectory is influenced by gender, ICS treatment, BMI, and asthma exacerbations. IL33 and GSDMB may be candidate genes for their lung function growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 25 publications
0
15
1
Order By: Relevance
“…Included studies 11 observational studies with a total of 3720 participants were included [28][29][30][31][32][33][34][35][36][37]. Four studies were in children (n=787) [28,30,34,36] and seven in adults (n=2933) [29, 31-33, 35, 37, 38]. Asthma was physician-diagnosed in eight studies (n=1044) [28, 30-34, 36, 37] and self-reported in three studies (n=2676) [29,35,38].…”
Section: Observational Studiesmentioning
confidence: 99%
“…Included studies 11 observational studies with a total of 3720 participants were included [28][29][30][31][32][33][34][35][36][37]. Four studies were in children (n=787) [28,30,34,36] and seven in adults (n=2933) [29, 31-33, 35, 37, 38]. Asthma was physician-diagnosed in eight studies (n=1044) [28, 30-34, 36, 37] and self-reported in three studies (n=2676) [29,35,38].…”
Section: Observational Studiesmentioning
confidence: 99%
“…Our sample is similar to that of a recent study in which 45.1% of children with asthma recruited in another local hospital in Hong Kong did not require ICS. 77 Our sample may therefore be representative of urban Asian families in general who are rearing children with a low severity of asthma. 78 Hence, we suggest that ACT integrated with asthma education could be universally adopted to help parents to improve their management of childhood asthma, regardless of the 6MFU, 6-mo follow-up after the intervention; AAQ-II, Acceptance and Action Questionnaire-II; Mdiff, difference in the estimated marginal means; -, not applicable.…”
Section: Days Per Week)mentioning
confidence: 99%
“…Several recent studies showed that high baseline FeNO was associated with reduced lung function growth in asthmatic children (47) and accelerated lung function decline in adults (48, 49). In the pediatric study from China 193 asthmatic children, mean age 9.7 years (SD 1.9 years) were followed for 5 years (47). One quarter had reduced lung function growth which was associated with lower baseline spirometry, higher FeNO and female sex.…”
Section: Introductionmentioning
confidence: 99%